A pathway for sustainable conversion of sunlight to hydrogen using proposed compact CPV system. (1st June 2018) - Burhan, Muhammad; Shahzad, Muhammad Wakil; Oh, Seung Jin; Ng, Kim Choon
Highlights: Compact CPV design for rooftop operation with master slave control. Low cost optical collimator based solar tracking sensor for CPV with 0.1° accuracy. 18% STH efficiency with CPV, twice the electrical efficiency of PV. 240.2 kW h m −2  year −1 energy and 5.11 kg m −2  year −1 H2 output, in tropical regions. Abstract: Solar energy being intermittent in nature, can provide a sustainable, steady and high density energy source when converted into electrolytic hydrogen. However, in current photovoltaic market trend with 99% conventional single junction PV panels, this cannot be achieved efficiently and economically. The advent of the multi-junction solar cells (MJCs), with cell-efficiency exceeding 46%, has yet to receive wide spread acceptance in the current PV market in form of concentrated photovoltaic (CPV) system, because of its system design complexity, limiting its application scope and customers. The objective of this paper is to develop a low cost compact CPV system that will not only eliminate its application and installation related restrictions but it is also introducing a highly efficient and sustainable photovoltaic system for common consumer, to convert intermittent sunlight into green hydrogen. The developed CPV system negates the common conviction by showing two times more power output than the flat plate PV, in tropical region. In addition, sunlight to hydrogen conversion efficiency of 18% is recorded for CPV, which is two times higher than alone electricity production efficiency of flat plate PV.